2022
DOI: 10.3390/nano12071060
|View full text |Cite
|
Sign up to set email alerts
|

The Photocatalytic Performance of Nd2O3 Doped CuO Nanoparticles with Enhanced Methylene Blue Degradation: Synthesis, Characterization and Comparative Study

Abstract: The growth of the textile industry results in a massive accumulation of dyes on water. This enormous rise in pigments is the primary source of water pollution, affecting the aquatic lives and our ecosystem balance. This study aims to notify the fabrication of neodymium incorporated copper oxide (Nd2O3 doped CuO) nanoparticles by combustion method for effective degradation of dye, methylene blue (MB). X-ray diffraction (XRD), Field emission Scanning electron microscopy (FESEM), Zeta potential have been applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…To scavenge , e − , h + and OH˙ active sites, ascorbic acid (AA), K 2 Cr 2 O 7 (Cr 2 O 7 2− ), NaCl (Cl − ) and C 3 H 8 O (IPA) were used, respectively. 58–60 Based on the observation presented in Fig. 14(b), it is evident that the use of IPA as a trapping agent leads to a substantial reduction in photodegradation, up to 85%.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…To scavenge , e − , h + and OH˙ active sites, ascorbic acid (AA), K 2 Cr 2 O 7 (Cr 2 O 7 2− ), NaCl (Cl − ) and C 3 H 8 O (IPA) were used, respectively. 58–60 Based on the observation presented in Fig. 14(b), it is evident that the use of IPA as a trapping agent leads to a substantial reduction in photodegradation, up to 85%.…”
Section: Resultsmentioning
confidence: 88%
“…To enhance photocatalytic activity, the recombination rate needs to be mitigated. [57][58][59] In general, superoxide radical (O 2 À ), electron (e − ), hole (h + ) and hydroxyl radical (OHc) are the four active species that contribute to photocatalytic dye degradation process. For assessing the underlying mechanism of the F doped CuO as photocatalyst under UV light irradiation, trapping tests for the active species were conducted during the photodegradation phase of 3 mol% F doped CuO, as depicted in the Fig.…”
Section: Impact Of Radicals' Scavenger On Photocatalytic Degradationmentioning
confidence: 99%
“…29,30 Hence to overcome such a problem, a possible approach to get over these restrictions, surface imperfections, bandgap moderation, and more probability of photogenerated e − /h + recombination is by doping of ZnO nanoparticles with metals (Cu, Ag, and CO). [31][32][33] In ZnO : Cu 2+ , interesting catalytic properties have been reported. 25 The current study aimed to prepare a novel sunlight-active green synthesized Cu doped ZnO (Cu@ZnO) nanocomposite by using the leaf extract of Azadirachta indica (neem) for the removal of NAP and ANT (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the energy gap could be narrowed by modifying surface defects by forming nano-composites 17 . A research revealed that CuO nanoparticles doped with Nd 2 O 3 had a remarkable photocatalytic efficacy, reaching up to 90.8% during a duration of 80 min, accompanied with a degradation rate of 0.0227 min −1 18 . On the other hand, from 90 to 100% degradation was detected for several dyes by silver NPs.…”
Section: Introductionmentioning
confidence: 99%